Linkage Of Organizational Learning Practices In Enhancing Operational Performance - A Case Study - Tay, Chee Siang (2005)
The aim of this paper is to advance the current state of activities in the studies of the linkage of organizational learning practices in enhancing the bottom-line performance outcome. It takes an exploratory case study approach on an organizationa, supported by relevant and available linkage models.